KEKERASAN PADA ANAK DALAM NOVEL A CHILD CALLED IT DAN THE LOST BOY - Adeline Grace M. Litaay; Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstrak. The study examines child abuse in Dave Pelzer’s two novels, A Child Called It and The Lost Boy. The study focuses on forms of child abuse experienced by the main characters in the two novels. The study is based on literary theory on character and characterization, psychological literature approach and concept and indication of child abuse. The study is descriptive qualitative. The object of study is child abuse experienced by Dave Pelzer as portrayed in both novels (2001, Orion Books Ltd, Indonesian version). The data were collected with close reading method and note-taking of the pages containing utterances and behaviour of the characters and the author’s narration that indicate or describe any manners of abuse on David as the victim and main character in both novels. The procedure of analysis includes describing the intrinsic aspects of the novels on character-characterization expressing the personality and behaviour of the main character in his interaction with other characters, examining the theme and characterization in the novel; the extrinsic aspect of the novel is examined with psychological approach based on the forms of abuse experienced by the main character. The study found that David,the main character of the novels A Child Called It and The Lost Boy, has experienced various forms of physical, psychological abuse and several forms of neglect by his own mother.Kata Kunci: : child abuse, forms of child abuse, neglect